Зниження витрат матеріалів та енергії при розробці сучасних абсорберів з регулярними насадками - Лаврова, Інна Олегівна (НТУ "ХПІ", 2006)
The article is devoted to intensification of process of absorption of Benzol hydrocarbons from coke gas. The aim was to decrease the hydrocarbons losses with the reverse coke gas. The possibility of further intensification by means of augment of gas speed by limiting of hydraulic resistance of the set-up with regard to its technological peculiarities has been shown
Keywords: скрубери; коксохімічні виробництва; апарати насадочні; конструкції форсуночного типу; насадки Z–подібні; установки бензольні